2015
DOI: 10.1089/brain.2015.0344
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Resting-State Brain Function Using Arterial Spin Labeling

Abstract: Arterial spin labeling (ASL) is an increasingly established magnetic resonance imaging (MRI) technique that is finding broader applications in studying the healthy and diseased brain. This review addresses the use of ASL to assess brain function in the resting state. Following a brief technical description, we discuss the use of ASL in the following main categories: (1) resting-state functional connectivity (FC) measurement: the use of ASL-based cerebral blood flow (CBF) measurements as an alternative to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 113 publications
(116 reference statements)
3
85
0
3
Order By: Relevance
“…However, PASAT performance increased fatigue levels at a similar rate for both HC and ME/CFS patients. The use of ASL represents an additional strength of our study because of its a) lower sensitivity to movement artifacts compared to BOLD fMRI; and b) direct measurement of CBF, which better reflects underlying neuronal activity [42]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PASAT performance increased fatigue levels at a similar rate for both HC and ME/CFS patients. The use of ASL represents an additional strength of our study because of its a) lower sensitivity to movement artifacts compared to BOLD fMRI; and b) direct measurement of CBF, which better reflects underlying neuronal activity [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Possible differences in image signal scaling factor between the PD and pCASL scans.. ASL images were visually inspected to ensure the absence of gross artifacts/abnormalities, resulting in the removal of one subject. ASL data have been shown to be less sensitive to motion effects than blood oxygenation level dependent (BOLD) fMRI [42], and the use of mean images across each segment reduces concerns regarding motion-related artifacts on CBF estimates. However, the Artifact Detection Toolbox [41] was used to identify 4D ASL volumes with excessive motion, resulting in the exclusion of one additional subject.…”
Section: Methodsmentioning
confidence: 99%
“…As BOLD is affected by macrovascular effects, CBF can reflect activity better in tissue capillary bed. Therefore, ASL CBF might be a more precise approach to measure differences in resting brain activity (5,10). In our study, ASL perfusion data were obtained by using 2D pCASL and concurrent BOLD contrast was used for rs-fMRI study instead of CBF time series.…”
Section: Resting State Fmrimentioning
confidence: 99%
“…Recently, several technologies have been developed to maximize the SNR of ASL, including background suppression (BS) and 3D sequences such as GRASE (a hybrid of gradient and spin echo). 3D acquisitions with BS offer increased SNR compared to 2D EPI sequences (10). With these advanced techniques, further studies are needed using CBF time series.…”
Section: Resting State Fmrimentioning
confidence: 99%
“…It has been shown that CBF is more closely related to neuronal activities through neurovascular coupling compared to BOLD signals (Chen et al, 2015). With careful adjustment of age related changes in gray matter volume and physiological parameters (Jain et al, 2012), region and sexspecific growth curves of CBF that diverge between the two sexes around puberty (Satterthwaite et al, 2014) have been observed.…”
mentioning
confidence: 99%